2022
DOI: 10.1155/2022/7537955
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Biologically Synthesized Copper Nanoparticles Show Considerable Degradation of Reactive Red 81 Dye: An Eco‐Friendly Sustainable Approach

Abstract: Diospyros kaki leaf extract was used in this study as a favorable basis for the synthesis of copper nanoparticles (Cu NPs). X-ray diffraction (XRD) and UV-visible spectroscopy approaches were used to characterize the biologically synthesized copper nanoparticles. The XRD analysis showed that copper nanoparticles were face-centered cubic structure. Various experimental levels like conc. of dye, concentration of Cu NPs, pH, reaction time, and temperature were optimized to decolorize reactive red 81 dye using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…AgNPs obtained through its extracts have been examined for antibacterial and antifungal activity. 45 , 49 55 In certain cases, even their catalytic activity in the degradation of dyes present in industrial wastewater like Reactive Yellow 160, 56 Direct Fast Rose FR Red 227, 57 Basic Brilliant Flavine Y-40, 57 Reactive Red 81, 58 Congo Red Direct, 59 Orange E3 60 and Crystal Violet 61 have been confirmed. Sun and his co-workers assessed the effects of time, optimal dosage of extract, and temperature on the synthesis of AgNPs (20–90 nm).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…AgNPs obtained through its extracts have been examined for antibacterial and antifungal activity. 45 , 49 55 In certain cases, even their catalytic activity in the degradation of dyes present in industrial wastewater like Reactive Yellow 160, 56 Direct Fast Rose FR Red 227, 57 Basic Brilliant Flavine Y-40, 57 Reactive Red 81, 58 Congo Red Direct, 59 Orange E3 60 and Crystal Violet 61 have been confirmed. Sun and his co-workers assessed the effects of time, optimal dosage of extract, and temperature on the synthesis of AgNPs (20–90 nm).…”
Section: Introductionmentioning
confidence: 93%
“…Tea leaves as a reach plant source of natural reducing compounds have gained recognition among the interests of researchers not only in terms of extraction but also in the synthesis of nanoparticles of various metals. Of all types of tea, green tea deserved special attention. AgNPs obtained through its extracts have been examined for antibacterial and antifungal activity. , In certain cases, even their catalytic activity in the degradation of dyes present in industrial wastewater like Reactive Yellow 160, Direct Fast Rose FR Red 227, Basic Brilliant Flavine Y-40, Reactive Red 81, Congo Red Direct, Orange E3 and Crystal Violet have been confirmed. Sun and his co-workers assessed the effects of time, optimal dosage of extract, and temperature on the synthesis of AgNPs (20–90 nm) .…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%